How demands and resources impact chronic fatigue in the maritime industry. The mediating effect of acute fatigue, sleep quality and recovery - Andrei, Daniela; Griffin, Mark; Grech, M.; Neal, A. (ELSEVIER, 2020)
The aim of the present study was to examine how different work demands and resources characteristic to the maritime industry are related to chronic fatigue in seafarers. Moreover, we investigated the role of different fatigue related processes, such as acute fatigue, sleep problems and inter-shift recovery in explaining the association between work characteristics and chronic fatigue. 199 seafarers working for the marine operations of a large global mining company participated in a cross-sectional survey design. Findings showed that working under time pressure and vigilance demands have differential relationships with chronic fatigue, with vigilance demands showing a stronger association. Moreover, this association was only partially mediated by fatigue processes, indicating that there might be several mechanisms involved. Social support emerged also as a critical job resource that can protect against fatigue, highlighting potential negative implications of current HR and staffing practices in the industry that discourage stable crews and might impair the development of supportive social climates onboard ships. Job autonomy also showed direct negative associations with chronic fatigue. Overall, our findings support the application of job demands – resources models to emphasize the importance of understanding the differential effects of work demands and resources characteristic to the maritime industry environment for seafarers’ chronic fatigue. Shipping companies should therefore consider the impact of these factors when trying to improve safety or wellbeing of the seafarers onboard their ships, given the critical role that chronic fatigue plays for both these outcomes.